European consensus-based interdisciplinary guideline for diagnosis and treatment of basal cell carcinoma-update 2023 - Peris, Ketty; Fargnoli, Maria Concetta; Kaufmann, Roland; Arenberger, Petr; Bastholt, Lars; Seguin, Nicole Basset; Bataille, Veronique; Brochez, Lieve; Del Marmol, Veronique; Dummer, Reinhard; Forsea, Ana-Marie; Gaudy-Marqueste, Caroline; et al. (European journal of cancer (Oxford, England, 2023)
Basal cell carcinoma (BCC) is the most common malignant tumour in white populations. Multidisciplinary experts from European Association of Dermato-Oncology (EADO), European Dermatology Forum, European Society for Radiotherapy and Oncology (ESTRO), Union Européenne des Médecins Spécialistes, and the European Academy of Dermatology and Venereology developed updated recommendations on diagnosis and treatment of BCC. BCCs were categorised into 'easy-to-treat' (common) and 'difficult-to-treat' according to the new EADO clinical classification. Diagnosis is based on clinico-dermatoscopic features, although histopathological confirmation is mandatory in equivocal lesions. The first-line treatment of BCC is complete surgery. Micrographically controlled surgery shall be offered in high-risk and recurrent BCC, and BCC located on critical anatomical sites. Topical therapies and destructive approaches can be considered in patients with low-risk superficial BCC. Photodynamic therapy is an effective treatment for superficial and low-risk nodular BCCs. Management of 'difficult-to-treat' BCCs should be discussed by a multidisciplinary tumour board. Hedgehog inhibitors (HHIs), vismodegib or sonidegib, should be offered to patients with locally advanced and metastatic BCC. Immunotherapy with anti-PD1 antibodies (cemiplimab) is a second-line treatment in patients with a progression of disease, contraindication, or intolerance to HHI therapy. Radiotherapy represents a valid alternative in patients who are not candidates for or decline surgery, especially elderly patients. Electrochemotherapy may be offered when surgery or radiotherapy is contraindicated. In Gorlin patients, regular skin examinations are required to diagnose and treat BCCs at an early stage. Long-term follow-up is recommended in patients with high-risk BCC, multiple BCCs, and Gorlin syndrome.
Keywords: proteiny hedgehog; Topical therapy; nádory kůže; bazocelulární karcinom; Consensus; Humans; Skin Neoplasms; Aged; Surgical therapy; senioři; lidé; Immunotherapy; Destructive therapy; Photodynamic therapy; Radiation therapy; konsensus; Hedgehog Proteins; Gorlin syndrome; Carcinoma, Basal Cell; Hedgehog inhibitors; Classification; Basal cell carcinoma; Electrochemotherapy; imunoterapie; Guidelines